Deferred pointwise f-statistical convergence of sequences of fuzzy mappings of order ? - Bayram, E.; Et, M.; Aydin, A. (Univ Sistan & Baluchestan, 2025)
This research paper introduces and investigates two new concepts, namely pointwise deferred f-statistical convergence of order alpha and strong pointwise deferred f-summability of order alpha, within the context of sequences of fuzzy mappings. The study explores the relationships between these newly proposed concepts and establishes several inclusion theorems. These findings contribute valuable insights into the properties of the introduced concepts, shedding light on their characteristics and applications in the realm of fuzzy mappings.
Keywords: Fuzzy number; fuzzy mappings; deferred statistical convergence; Cesa`ro summability; pointwise statistical convergence